OTOTOXIC EFFECTS OF ANTINEOPLASTIC DRUGS: A SYSTEMATIC REVIEW - Monica, Desnita (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: When scientific evidence is reviewed, platinum-based chemotherapeutics are essential in cancer treatment at various levels and are the most referenced ototoxic drugs. Aim: This study aims to give scientific data based on a PRISMA systematic literature review to standardize information on the ototoxic effects of antineoplastic medicines. Methods: A combination based on the Medical Subject Heading Terms (MeSH) was utilized to choose studies. The databases Medline (Pubmed), LILACS, SciELO, SCOPUS, WEB OF SCIENCE, and BIREME were used without regard to language, period, or region. The quality of the papers was evaluated, and articles with a minimum score of 6 on the modified literature scale were included. The selected studies had descriptive, cohort, and cross-sectional designs connected to the research purpose. Results: The results of this systematic review included three papers. The ototoxicity caused by cisplatin alone ranged from 45% to 83.3%, while that caused by carboplatin usage ranged from 16.6% to 75%. The cumulative dosages of these antineoplastic drugs, both alone and in combination, varied significantly. After therapy, there were noticeable changes in hearing, particularly at high frequencies. Conclusion: Auditory alterations were observed following the administration of platinum-based antineoplastic medicines; nevertheless, there was significant variation in the frequency of ototoxicity and the cumulative dose of the drugs administered.